2015
DOI: 10.1111/jai.12950
|View full text |Cite
|
Sign up to set email alerts
|

Fish detection around offshore artificial structures: preliminary results from hydroacoustics and fishing surveys

Abstract: The spatial distribution of fish assemblages was investigated through either hydro-acoustic surveys (using a Multibeam Echosounder) or fishing surveys (using trammel nets) carried out at increasing distance from two gas extraction structures in the Adriatic Sea and characterized by different building architecture: one, a four-leg platform; the other a subsea well-site. Both types of surveys were monthly and performed for 1 year starting after installation of the structures. Primary scope of the study was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…using gillnets (Løkkeborg et al, 2002), trawling (Fujii, 2015), remotely operated vehicles (Ajemian et al, 2015;Todd et al, 2018), tag and release (Wright et al, 2020), hydroacoustics (Gallaway et al, 2021;Punzo et al, 2015), and scientific angling (Karnauskas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…using gillnets (Løkkeborg et al, 2002), trawling (Fujii, 2015), remotely operated vehicles (Ajemian et al, 2015;Todd et al, 2018), tag and release (Wright et al, 2020), hydroacoustics (Gallaway et al, 2021;Punzo et al, 2015), and scientific angling (Karnauskas et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the different benthic organism populations observed in different types of ARs indicated that the shape and structure of ARs may have impacts for biological communities living on them and their productivity. This phenomenon was highlighted by Punzo et al (2015), who found that aggregation effect of ARs on fish assemblages is related to the bulk volume and building architecture of the structures. The ARs are effective in aggregating benthos and in holding them by Table 3 Particle size analysis of benthic samples taken from study area.…”
Section: Echo-sounder Dataset Mining For Arsmentioning
confidence: 94%
“…These information can assist the managers to make a reasonable evaluation on the effectiveness of ARs combined with biological data (e.g. abundance and biomass) and abiotic data such as temperature, pH, oxygen, and salinity (Punzo et al, 2015;Schygulla and Peine, 2013). In addition, this can provide reference for the future construction of ARs and help local managers to better monitor coastal waters.…”
Section: Echo-sounder Dataset Mining For Arsmentioning
confidence: 99%
“…The role that a platform's jacket plays as fish and invertebrate habitat can be part of that decision-making process [1], and the increasing number of platforms to be decommissioned increases the need for this information. Historically, these characterizations have come from targeted biological surveys (e.g., conducted by scuba divers, manned submersibles, remotely operated vehicles (ROVs), bioacoustics, and nets) of a limited number of offshore oil and gas structures [2][3][4][5][6][7]. However, there also exists oil and gas ROV engineering surveys of platforms and associated infrastructure (i.e., pipelines, subsea equipment and wellheads) conducted as part of routine physical integrity inspections.…”
Section: Introductionmentioning
confidence: 99%